FORMULASI DAN EVALUASI SEDIAAN MASKER GEL PEEL OFF PATI BENGKOANG (pachyrrhizul erosus.L) UNTUK FLEK HITAM BEKAS JERAWAT - Dian Mardiana Hanan; Astria Nur Puji H (STIKes Muhammadiyah Kuningan, 2018)
Flavonoid and saponins can remove black spots on the skin. Jicama (pachyrhizus erosus.L) contains high enough phenolic substances. The aim of this research is formulatied peel off gel mask from the right jicama starch which produced peel off gel mask product effectively, stable, safe, in use. Formulation of peel off gel mask was made with a PVA base with different concentrations of 10%, 15%, 20%. Evaluation of peel off gel mask preparation includes observation of homogeneity test, organoleptic test, pH test, dry time test, adhesion test, for 2 weeks at room temperature ie 25⁰-30⁰C. The results of the evaluation test showed that all gel preparations of peel off gel masks are stable in the consistency, color and odor aspects. The peel off gel mask has a stable pH. The results of the evaluation test showed that gel preparation peel off gel of formula 3 is the most homogeneous and stable and faster drying time.